Identification and molecular detection of the pathogen of Phalaenopsis leaf yellowing through genome analysis - Tsao, Wei-Chin; Li, Yi-Hsuan; Tu, Yi-He; Nai, Yu-Shin; Lin, Tsung-Chun; Wang, Chih-Li (Frontiers in Microbiology, 2024)
Moth orchids (Phalaenopsis spp.) are globally popular ornamental flowers. However, effective management strategies for Phalaenopsis leaf yellowing remain elusive, making the fungal disease a challenging obstacle affecting moth orchids at various growth stages. This disease manifests as collar rot, leaf yellowing, leaf abscission, and eventually, plant death. The lack of effective management strategies is likely attributed to a limited understanding of the disease pathogenesis and pathogen dissemination pathways. In this study, we established Fusarium phalaenopsidis sp. nov. was established in this study to stabilize the classification status of PhalaenopsisPhalaenopsis leaf yellowing pathogens using molecular and morphological features. The genome of the holotype strain was sequenced and assembled, revealing its genome structures. Our aAnalyses of virulence-related elements, including transposon elements, secondary metabolite biosynthetic gene clusters, effectors, and secreted carbohydrate-active enzymes, shed light on the potential roles of three fast core chromosomes in virulence. Through comparative genomics and blast screening, we designed tTwo species-specific primers were designed based on unique gene sequences of two virulence-related proteins through comparative genomics and BLAST screening. The specificity of these primers was validated using isolates of F. phalaenopsidis, non-target species in the Fusarium solani species complex, other Fusarium species complexes, and saprophytic fungi. These results are intended to accelerate the identification of the pathogens, facilitate the study of disease pathogenesis, and pave the way for elucidating pathogen dissemination pathways. Ultimately, they aim to contribute to the formulation of effective control strategies against PhalaenopsisPhalaenopsis leaf yellowing.